EVALUASI TUGAS PENYULUHAN PERIKANAN DI KECAMATAN SANGKULIRANG - Pauzan Kurniawan; Fitriyana; Qoriah Saleha (Asosiasi Dosen Muda Indonesia, 2022)
The purpose of this study was to evaluate the level of implementation of the duties of the fishery instructor in Sangkulirang District based on the indicators of the extension worker in carrying out the duties and functions of the fishery instructor (East Kutai Regent Regulation number 56 of 2014: article 5. This type of research is a quantitative descriptive research type. The research method used is survey method. The population in this study were Fisheries Extension Officers in Sangkulirang Sub-district with a total of 3 people. The sample was determined by census, meaning that the three Fisheries Extension Officers were sampled. The results of the evaluation of the tasks of the Sangkulirang Fisheries Extension Officer based on the East Kutai Regent Regulation number 56 of 2014: article 5 cumulatively is in the high category with a value of 40.99 which is between 39.68-51.00. This value can be interpreted that the task of the fishery instructor in Sangkulirang District has been carried out well, although not yet optimal.